Photo of Ekvira Devi on the walls of a Koli home - Mumbai Archive Project Team (Jio Institute, 2024)
For many Koli families, their kula devata is Ekvira Devi, regarded as a manifestation of the goddess Renuka. Kolis make a yearly pilgrimage to Ekvira Devi Temple at the Karla Caves, near Lonavala.